2020
DOI: 10.1038/s41598-020-63835-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of amino acid metabolism in response to nitrogen deficiency and nitrogen forms in tea plant root (Camellia sinensis L.)

Abstract: Free amino acids, including theanine, glutamine and glutamate, contribute greatly to the pleasant taste and multiple health benefits of tea. Amino acids in tea plants are mainly synthesized in roots and transported to new shoots, which are significantly affected by nitrogen (N) level and forms. However, the regulatory amino acid metabolism genes have not been systemically identified in tea plants. Here, we investigated the dynamic changes of free amino acid contents in response to N deficiency and forms in tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 71 publications
2
71
2
Order By: Relevance
“…AAATs catalyze l - phenylalanine into phenylpyruvic acid in tea plants, and CsAAAT2 was proposed as the key one [ 28 ]. The expression of CsPAL and CsAAAT2 under long-term N fertilization was significantly lower than that with no N fertilization ( Figure 5 B), consistent with previous studies on the effect of N application on tea plants using RNA-Seq [ 13 , 19 , 59 ]. From the above results, we hypothesized that, on the one hand, as a result of long-term N application, the accumulation of chlorophyll in tea leaves increased and more carbon-containing compounds were used to synthesize amino acids, while the concentration of substrate for the synthesis of polyphenols was relatively reduced, which led to the reduction in the content of catechins; on the other hand, the down-regulation of CsPAL and CsAAAT2 involved in the l -phenylalanine pathway might be the main factor leading to the decrease of these metabolites in this pathway.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…AAATs catalyze l - phenylalanine into phenylpyruvic acid in tea plants, and CsAAAT2 was proposed as the key one [ 28 ]. The expression of CsPAL and CsAAAT2 under long-term N fertilization was significantly lower than that with no N fertilization ( Figure 5 B), consistent with previous studies on the effect of N application on tea plants using RNA-Seq [ 13 , 19 , 59 ]. From the above results, we hypothesized that, on the one hand, as a result of long-term N application, the accumulation of chlorophyll in tea leaves increased and more carbon-containing compounds were used to synthesize amino acids, while the concentration of substrate for the synthesis of polyphenols was relatively reduced, which led to the reduction in the content of catechins; on the other hand, the down-regulation of CsPAL and CsAAAT2 involved in the l -phenylalanine pathway might be the main factor leading to the decrease of these metabolites in this pathway.…”
Section: Discussionsupporting
confidence: 90%
“…N application can improve the nutrient supply from the soil, thereby preserving the normal physiological metabolism of tea plants, which is very important for maintaining tea quality and yield [ 13 ]. According to official statistics, high N application cultivation is universal in tea plantations in China; the national average application is 491 kg/hm 2 N per year [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome data of nitrogen nutritional stress in the CsPAO gene family were published by our laboratory (Yang et al, 2020). In the control group, tea seedlings were hydroponically cultured with Shigeki Konishi nutrient solution.…”
Section: Transcriptome Data Analysismentioning
confidence: 99%
“…wileyonlinelibrary.com/jsfa NH 4 + , 45 thus the application of nitrogen fertilizers and organic matter (urea) has also been practiced in tea plantations. 46,47 A recent study reported that organic fertilizer significantly increased the amino acid content of tea.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of nutrients is highly associated with tea plants productivity and quality 44 . Tea plants preferentially assimilate NH 4 + , 45 thus the application of nitrogen fertilizers and organic matter (urea) has also been practiced in tea plantations 46,47 . A recent study reported that organic fertilizer significantly increased the amino acid content of tea 48 .…”
Section: Discussionmentioning
confidence: 99%